Sperm DNA Integrity Assessment: A New Tool in Diagnosis and Treatment of Fertility - Mona Bungum (Hindawi Limited, 2012)
Infertility affects 15% of all couples. Although male infertility factors with reduced semen quality are contributing to about half of all involuntary childlessness, the value of standard semen parameters in prediction of fertility in vivo and choice of proper method for assisted reproduction is limited. In the search for better markers of male fertility, during the last 10 years, assessment of sperm DNA integrity has emerged as a strong new biomarker of semen quality that may have the potential to discriminate between infertile and fertile men. Sperm DNA Fragmentation Index (DFI) as assessed by the flow cytometric Sperm Chromatin Structure Assay (SCSA) can be used for evaluation of sperm chromatin integrity. The biological background for abnormal DFI is not completely known, but clinical data show that DFI above 30% is associated with very low chance for achieving pregnancy in natural way or by insemination, but not in vitro. Already when the DFI is above 20%, the chance of natural pregnancy may be reduced, despite other sperm parameters being normal. Thus this method may explain a significant proportion of cases of unexplained infertility and can be beneficial in counselling involuntary childless couples need of in vitro fertilisation.